Children’s velo-mobility – how cycling children are ‘made’ and sustained. - Carstensen, Trine Agervig; Nielsen, Thomas A. Sick; Olafsson, Anton Stahl (Proceedings from the Annual Transport Conference at Aalborg University, 2014)
Sustainable mobilities play a dominate role in low carbon futures and cycling is an integral element. Children are heirs of transport cultures and crucial for future sustainable mobility. Moreover cycling is important for children’s independent mobility and geographical experience. Dominating approaches in transport research, including cycling, understand travel behaviour individualistic and lack to grasp the relational complexities, which are inevitable when considering children’s mobilities. Furthermore has children’s cycling largely been studied as independent mobility and active school travel. How cycling is learned and constituted, and how cycling skills are consolidated, extended and turned into a stabilized practice remains unstudied. Drawing on in-depth interview data from the region of Copenhagen, Denmark, among families with children (N=20) the paper provides new insights into how children, parents, and the locale socio-spatial environment through collaborations, negations and experiments co-produce independent cycling. It introduces a three-step model for conceptualizing children’s cycling deriving from processes of gradually enlarging the geographical experience and partial embodying of know-how of traffic power relations and mobility technology. The paper examines how parents’ perception of risks are transgressed by cycle training and how cycling is fitted into complex household routines. By shedding light on the sensitive mechanisms that ‘make’ and sustain cycling children the paper inform a discussion of urban planning and transport policy measures important for stabilizing sustainable mobility.